Independent Heath Facility Meets Cancer Care Ontario and Canadian Association of Gastroenterology Guidelines for Endoscopic Procedure Wait Times While Meeting Quality Indicators: A Retrospective Review - Fraser Kegel; Niv Sne; Timothy Rice; Eric Joy; Shayan Shahsavar; Celeste A. Collins; Maria Gagarine; Alexandra Allard-Coutu; Lisa Klotz; Angela Coates; Kamyar Kahnamoui; Marko Simunovic (Canadian Journal of Gastroenterology and Hepatology)
Background. Canadian independent health facilities (IHFs) have been implemented to reduce hospital endoscopy volume and expedite endoscopic evaluations for patients suspected to have underlying colorectal cancer. Methods. We conducted a retrospective review of a prospective database at a large-volume urban IHF. The primary outcomes were wait times, and the secondary outcomes were colonoscopy quality indicators and complication rates. Results. Median wait times from referral to colonoscopy met the recommendations set out by the Canadian Association of Gastroenterology and Cancer Care Ontario for all indications: chronic abdominal pain: 43 days; new onset change in bowel habits: 36 days; bright red rectal bleeding: 42 days; documented iron-deficiency anemia: 43 days; fecal occult blood test positive: 38 days; cancer likely based on imaging or physical exam: 23 days; chronic diarrhea and chronic constipation: 42 days; and screening colonoscopies: 55 days. Secondary outcomes of quality indicators and complication rates all met or exceeded the CCO and CAG recommendations. Conclusions. This IHF met the recommended wait times for all indications for colonoscopy while maintaining high procedural quality and safety. IHFs are one solution to help meet the increasing demand for colonoscopy in Ontario.